Description of the puparium of Barbiellinia hirta Bezzi (Diptera, Stratiomyidae), and the record of parasitism by Monomachus cubiceps Schrottky (Hymenoptera, Monomachidae) - Pujol-Luz, José Roberto; Godoi, Fabio Siqueira Pitaluga De; Waichert, Cecilia; Barros-Cordeiro, Karine Brenda (Zootaxa, 2025)
The puparium of Barbiellinia hirta Bezzi, 1922 is described, based on two specimens reared in the laboratory under controlled conditions until the adults emerged. The larva of B. hirta is the second immature stage of Chiromyzinae found in the Neotropical Region and has very distinct characters from the larva of Chiromyza vittata Wiedemann, 1820. Here we describe the puparium of B. hirta, compare it to the puparium of C. vittata and present the first record of parasitism in Barbiellinia Bezzi by the parasitoid wasp Monomachus cubiceps Schrottky, 1911, as well as updating the records of the geographical distribution of the genus Barbiellinia.